Effect of phytoremediation on the morpho-anatomical characters of some aquatic macrophytes - JONES T NAPALDET; INOCENCIO Jr E BUOT; MACRINA T ZAFARALLA; IRENEO Jr. L LIT; RACHEL C SOTTO (Society for Indonesian Biodiversity, 2019)
Abstract. Napaldet JT, Buot Jr. IE, Zafaralla MT, Lit Jr. IL, Sotto RC. 2019. Effect of phytoremediation on the morpho-anatomical characters of some aquatic macrophytes. Biodiversitas 20: 1289-1302. In constructed wetland studies, the effect of pollutants or the phytoremediation set-up on aquatic macrophytes is often not investigated. This literature gap may prove useful in realizing the full phytoremediation potential of aquatic macrophytes. This study was conducted to examine the effect of phytoremediation, the set-up, and the pollutants, on the morpho-anatomical characters of aquatic macrophytes used in the constructed wetlands. This was investigated in Amaranthus spinosus, Eichhornia crassipes, Eleusine indica, and Pennisetum purpureum. Simultaneously, interesting anatomical features in the aquatic macrophytes were discovered. Anomalous secondary growth was discovered in roots and stems of A. spinosus while isobilateral anatomy of the leaf with two layers of vascular bundles and two palisade layers under each epidermis were noted in E. crassipes. The anatomy of P. purpureum was also first reported here. Results showed that the response of the aquatic macrophytes toward phytoremediation treatments was species-specific. E. indica and P. purpureum were the ones significantly affected by the phytoremediation treatment in contrasting ways. E. indica under phytoremediation suffered significantly lower growth rate than those in the uncontaminated site which could be attributed to the inability of its relatively short root system to tap into the water and nutrients. On the other hand, P. purpureum exhibited higher biomass and growth rate under phytoremediation treatment which is primarily due to the water pollutants absorbed as nutrients by the plant. There were no structural differences observed in the anatomy of the aquatic macrophytes between sampling sites except in E. indica. The root’s cortex in samples under phytoremediation has no aerenchyma while this is present in uncontaminated site and Balili River samples. This shows that, indeed, some aquatic macrophytes were significantly affected (p=0.00) by phytoremediation that should be taken in consideration when planning and designing constructed wetlands.